Decentralized AC Optimal Power Flow Problem Considering Prohibited Operating Zones - Do Carmo Yamaguti, Lucas [UNESP] (2022)
The Optimal Power Flow (OPF) problem is commonly formulated considering one central operator manager (centralized approach). However, in practice, the power system is structured by interconnected areas, controlled by several system operators, which are dependent on their neighbors and must exchange sensitive data with each other. In addition, some generation units must be restricted in some zones of operation to avoid negative operational effects. This paper proposes a mixed-integer nonlinear programming model to solve the decentralized AC-OPF considering prohibited operation zones (POZ). A matheuristic algorithm based on the variable neighborhood descent heuristic method is used to deal with the integer variables of the problem, while a non-linear optimization solver is used to solve the optimal power flow with continuous variables. The proposed model and solution technique are validated using the IEEE 118-bus system, ensuring that the decentralized model determines solutions close to the centralized model without and with POZ constraints.